Heavy Metals Removal Using Activated Carbon, Silica and Silica Activated Carbon Composite - Kabbani, Ahmad (2014)
Heavy metal pollution has become one of the most serious environmental problems nowadays. The removal of heavy metals from the environment is of special concern due to their persistence. Batch experiments were conducted to test the ability of activated carbon for the removal of lead, cadmium, nickel, chromium and zinc from water. The Langmuir and Freundlich adsorption isotherms were used to verify the adsorption performance. Nickel showed the highest removal percentages by activated carbon at all concentrations and the removal percentages decreased as the concentration of heavy metal increased. The obtained correlation coefficient (R2) for different adsorbents suggested poor fitting of the experimental data to Langmuir isotherm for Cd, Pb, Ni, and Zn, while R2 obtained using Freundlich model for different adsorbents indicated that it fitted the experimental data well. Silica/activated carbon (2:3) composite was more efficient in the removal of nickel ions than activated carbon and silica nanoparticles. SEM pictures were taken for the three particles under test.